Deep nitrogen fertilizer placement improves the yield of summer maize (Zea mays L.) by enhancing its photosynthetic performance after silking - Yi Cheng; Xiao-Ying Chen; Hao Ren; Ji-Wang Zhang; Bin Zhao; Bai-Zhao Ren; Peng Liu (BMC Plant Biology)
Abstract Background Effective nitrogen (N) fertilizer management can improve photosynthetic performance of maize and enhance the grain yield. However, the effects of the deep placement of N on post-silking photosynthetic performance in maize and its relationship with grain filling are limited. The study was a split-plot design with N application rates as the main plots and N placement depths as sub-plots. The N application rates consisted of 225, 191.25, and 157.5 kg ha− 1 and N placement depths consisted of 5 and 15 cm, respectively. The growth parameters, photosynthetic capacity, subcellular ultrastructure, antioxidant system in maize leaves, and grain filling characteristics were measured. Results Increasing the N placement depth counteracted the adverse effects of reduced N availability on the leaf area index, leaf area duration, and photosynthetic performance of plants. Compared to 225 kg N ha− 1 applied underground at 5 cm, a 15% reduction in the N application rate at 15 cm reduced oxidative stress through the activation of antioxidative enzymes, which enabled plants to maintain their chloroplast ultrastructure, achieving 20.7% higher chlorophyll content, 7.8% higher photosynthetic rate per unit of leaf area, and 5.6% higher leaf area index during the later growth period. It also facilitated enhancing the growth rate during maximum filling and extending the active filling duration of grains. Conclusions Overall, reducing the recommended N application rate of 225 kg ha− 1 by 15% but applying it at a depth of 15 cm might delay plant senescence and extend grain filling active time, improved photosynthetic performance in late growth period, and finally increased grain weight and grain yield of maize.